Innovation through Collaborative Partnerships: Creating the MSN News for iPad App at VanceInfo Technologies. Issue 1 (June 2013) - Abbott, Pamela; Zheng, Yingqin; Du, Rong
This teaching case focuses on a collaborative project between a major software and services outsourcing company in China (VanceInfo Technologies) and one of its major Western clients (Microsoft Inc.). VanceInfo and Microsoft had been engaged in a long-term client/vendor relationship since 1997 and the project had been the result of this long-term partnership arrangement. The project was deemed quite successful and innovative; hence it provided an opportunity to determine how collaborative innovation could work between two remote and culturally different supply chain partners and how the lessons from this project could be used to inform SSO providers of ways in which they could move up the value chain to more client-focused value added services. The case looks in-depth at the actual working practices that enabled the distributed Microsoft/VanceInfo team to produce a market-led innovative product. Agile methods were highly integral to the functioning of those work practices and are quite carefully scrutinised from the point of view of how they were adapted for use in a distributed, cross-cultural environment. Users of the case study will be asked to formulate answers to several questions geared towards providing general guidelines that SSO providers can follow to achieve similar successful outcomes.